Communication—Direct Observation of the Shuttle Phenomenon in Lithium-Sulfur Batteries via the Digital Holographic Method. Issue 11 (6th September 2018) - Dai, Hongliu; Yuan, Boyu; Bai, Changyun; Lai, Chao; Wang, Chao
Abstract : Lithium-sulfur (Li-S) batteries are regarded as the best potential-energy storage systems because of their ultra-high energy density. However, their electrochemical performance is limited by the well-known shuttle effect. We used an online digital holography method to investigate the interfacial changes between the electrode and the electrolyte. An in-situ observation of the shuttle process was achieved in Li-S batteries. This result confirms the existence of the shuttle mechanism, and aids in the selection of preferable composite cathodes and electrolytes to produce high-performance Li-S batteries.